(untitled) (ModaPalavra e-periódico, 2020)
Fashion is a place of production of meaning in which social values are concretized plastically, enabling the transmission of the most varied and often antagonistic discourses. In this way several social groups are c onstituted with contesting narratives or reaffirming hegemonic values and tendencies, confirmed plastically in the adopted dress systems. In the wake of this thought we aim to analyze the discursive resources used by the collective Estileras on its page in a social media. This collective is positioned as a “place” for experimentation and transgression of dress norms sanctioned by contemporary society. The theoretical framework of Discursive Semiotics, developments in sociosemiotics and Michel Foucault’s not ions of power will be adopted in order to account for the complexity of the verb - visual discourses exposed by the collective.